Heavy‐resistance exercise‐induced increases in jump performance are not explained by changes in neuromuscular function. (6th December 2015) - Thomas, K.; Toward, A.; West, D. J.; Howatson, G.; Goodall, S.
Abstract : Post‐activation potentiation (PAP) is the increased involuntary muscle twitch response to stimulation following strong contraction. The enhancement to whole‐body explosive muscular performance (PE) after heavy‐resistance exercise is often attributed to modulations in neuromuscular function that are proposed to reflect PAP, but the evidence to support this is equivocal. We assessed the neuromuscular basis of PE using transcranial magnetic stimulation (TMS) of the primary motor cortex, and electrical stimulation of the femoral nerve. Eleven male athletes performed heavy‐resistance exercise with measures of countermovement jump (CMJ) pre‐ and 8 min post‐exercise. Pre‐exercise and after the final CMJ, single‐ and paired‐pulse TMS were delivered during submaximal isometric knee‐extensor contractions to measure corticospinal excitability, short‐interval intracortical inhibition (SICI), and intracortical facilitation (ICF), with motor evoked potentials recorded from rectus femoris. Twitch responses to motor nerve stimulation during and post maximum‐knee‐extensor contractions were studied to quantify voluntary activation (VA) and potentiated twitch ( Q tw, pot ). The experimental protocol successfully induced PE (+4 ± 1% change in CMJ, P  = 0.01), but no changes were observed for maximum voluntary force, VA, corticospinal excitability, SICI or ICF (all P  > 0.05), and Q tw, pot declined ( P  < 0.001). An enhancement of muscular performance after heavy‐resistance exercise was not accompanied by PAP, or changes in measures of neuromuscular function.